The Relationship Between Cognitive Achievement And The Accuracy of Performing Some Artistic Skills In Volleyball in Young Players - Star, Khalil; Muhammed, Jasem (Journal of Physical Education, 2018)
The Relationship Between Cognitive Achievement And The Accuracy of Performing Some Artistic Skills In Volleyball in Young PlayersThe importance of the research lies in learning and presenting correct information with ease as well as motivation students to learn. The problem of the research lies in the traditional styles used in providing volleyball knowledge to young players as well as the lack of using modern techniques that develop the player's achievement. The researchers aimed at identifying the relationship between cognitive achievement and skill performance in volleyball. The researcher used the descriptive method. The sample was (48) while the subjects were (28) young volleyball players aged (12 – 14) years old from the national center for gifted in volleyball. The data was collected and treated using proper statistical operations. The researchers concluded that players have the ability to develop their cognitive achievement and the skill performance. Finally they recommended making similar studies on other age groups and different training positions.